A wind turbine sensorless automatic control systems, analysis, modelling and development of IDA-PBC method - Hamiani Hichem; Mansouri Abdellah; Tadjeddine Ali Abderrazak; Belaidi Abdelkader; Salim Ramzi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Several non-linear controls are developed for controlling a wind energy conversion system equipped with a DFIG double feed asynchronous generator. Exploitation of the aerodynamic power captured by the turbine gives a new instruction to the controller based on passivity by keeping the hypersynchronous regime of the DFIG. An adaptive observer MRAS was developed for the considered as a structure in which the rotor speed is estimated from the measurement of stator and rotor currents. Our goal is to maximize active power, minimize construction costs in order to control wind turbine systems using our passivity and observation method. Best results were obtained using sensorless MPPT and IDA-PBC methods.